THE TRADITIONAL TOOLS AND IMPLEMENTS USED IN MAKING POTTERY: A CASE STUDY OF LONGPI POTTERY. - 1 LR Worchuirin Kazingmei, 2 Dr. Jacob Luiram (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Longpi is a general reference to two villages (Longpi Kajui and Nungpi Khullen) in ukhrul district of the Indian state of Manipur. Longpi is about 36 kilometres north of ukhrul, connected by national highway 150. Longpi is surrounded by Sihai in the east, Lunghar in the south, Phungcham, paorei and Peh in the west and Kalhang and Kuirei in the north. Longpi is famous for age old traditional pottery known as Longpi ‘Ham-Pai’. One unique feature of longpi pottery is that the potters make pottery without using potter’s wheel. They still practice the traditional technique of pottery making. It is believed that Longpi Ham-Pai used to be the main cooking utensils and storing foodstuff even for the other neighboring Naga tribes such as the Chakhesang, and Marams before the advent of aluminium and steel pots. Longpi Ham is made from a mixed paste of ground black serpentine stone and a special brown clay. As claimed by the locals, the clay is native to only Longpi village. The black serpentine rock and brown clay are mixed in the ratio three: two if the clay is collected from inside the pit, but if the clay is collected from the ground the ratio is three: three. The mixture is made into a paste by adding water. The shaping of the pot has two steps, (a) shaping the upper portion and (b) shaping the base of the pottery. Depending on the size and design wanted, pots are formed using different techniques. At the time of mixing of the materials, the potters have to cautiously check the presence of other impurities in the paste as it would cause the pots to explode during firing. The following tools are used in the indigenous Longpi pottery. They are: (a) Sopkai, (b) Kapa, (c) Lung-Masam and Lung-Rar, (d) Shimkhur and Suk, (e) Hakha-Naya, (f) Lee-Khu, (g) Ham-Masham, (h) Ham-Khalao, (i) Ham-Matom, (j)Ham-Khalang, (k) Ham-Kapi, (l) Ham-Lel, and (m) Ham-Tadan. At the time of firing, the potters used special tree leaves known as ‘Machi-Ni’. The shine of the pottery is produced by polishing with these leaves.